Perceived social support and global self-worth in adolescents - Chua, Yee Chii; Chua, Bee Seok; Agnis Sombuling (Persatuan Psikologi Malaysia, 2017)
The current study aimed to examine the importance of perceived social support from parents, peers, and teachers in relation to the adolescent’s global self-worth. A self-report survey was administrated to a total of 100 adolescents in a public high school. Data were collected by using Social Support Scale for Children and Adolescence (SSSCA) and Self-Perception Profile for Adolescents (SPPA). The validity and reliability of questionnaires were verified. The Standard Multiple Regression analysis was conducted to determine the best predictor of global self-worth among adolescents. The results of the analysis indicated that this combination of variables significantly predicted global self-worth, F (3, 96) = 5.97, p < 0.01. Surprisingly, the finding revealed that the peer support makes a significant contribution to the prediction of global self-worth, (β = .322, p < 0.01). While, there were no significant contribution of parent and teacher support towards global self-worth among adolescents. The conclusions and implications in the impact of the social support and the global self-worth were discussed.